The Influence of Teacher Strategies in Utilizing the Kekhatuan Semaka Museum as a Learning Resource on Students' Learning Interests - Adi Sanjaya; Risma Margaretha Sinaga; Novia Fitria Istiawati (MultiTech Publisher, 2024)
Museums that have important values and can be learned for students with in history learning. Teachers can see this as a source of historical learning by utilizing museums as a forum for learning that is contextual to regional culture. For this reason, it is necessary to take advantage of the kekahtuan semaka museum. This study aims to find out 1) teacher strategies for designing social studies learning on student learning interests; 2) implementation of learning resources to students' learning interests; 3) the effectiveness of the Semaka khatuan museum as a learning resource for students' learning interests; 4) implementation of teacher strategies, Semaka khatuan museum as a learning resource and social studies learning resource for students' learning interests. This research is a quantitative research. The research was conducted at SMP N 1 Bandar Negeri Semoung with a sample of 89 students. The results showed that 1) The teacher's strategy of designing social studies learning based on students' learning interests had a positive influence with probability results of 0.009 and tcount of 2.781; 2) Implementation of learning resources on students' learning interests, there is a positive influence with a probability result of 0.005 and tcount 2.712; 3) The effectiveness of the Semaka khatuan museum as a learning resource on students' learning interests, there is a positive influence with a probability of 0.003 and a calculation of 2.619; 4) The implementation of teacher strategies, the Kekhatuan Semaka Museum as a source of learning and social studies learning resources on the learning interests of students, has a positive influence with the results of a coefficient of 0.000, fcalculate 11.477 with a change of 81.8%. While 18.2% is influenced by other factors on students' interest in learning social studies.